2015
DOI: 10.4103/0366-6999.168043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Joint Line Elevation after Posterior-stabilized and Cruciate-retaining Total Knee Arthroplasty on Clinical Function and Kinematics

Abstract: Background:Joint line (JL) is a very important factor for total knee arthroplasty (TKA) to restore. The objective of this study was to evaluate the early clinical and kinematic results of TKAs with posterior-stabilized (PS) or cruciate retaining (CR) implants in which the JL was elevated postoperatively.Methods:Data were collected from patients who underwent TKA in our department between April 2011 and April 2014. The patients were divided into two groups based on the prosthesis they received (PS or CR). At 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
2
21
1
1
Order By: Relevance
“… 3 , 4 , 9 Although subsequent studies reported the acceptable critical range as sd 5 mm, 8 , 11 more recently opinion in the literature on this subject has been changed by newer reports indicating that a deviation of more than 4 mm in the joint line proximally or distally from its normal position leads to unfavourable results. 10 - 13 , 14 - 16 Thus, it is clear that exact determination of the anatomical joint line is essential to achieve an optimal post-operative clinical outcome. We believe that the anatomical joint line can be restored within the acceptable zone of less than 5 mm proximally or distally from its neutral/original anatomical position by using this simple, and reproducible method that we have presented herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 4 , 9 Although subsequent studies reported the acceptable critical range as sd 5 mm, 8 , 11 more recently opinion in the literature on this subject has been changed by newer reports indicating that a deviation of more than 4 mm in the joint line proximally or distally from its normal position leads to unfavourable results. 10 - 13 , 14 - 16 Thus, it is clear that exact determination of the anatomical joint line is essential to achieve an optimal post-operative clinical outcome. We believe that the anatomical joint line can be restored within the acceptable zone of less than 5 mm proximally or distally from its neutral/original anatomical position by using this simple, and reproducible method that we have presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…This issue still remains an object of interest. 9 - 11 The present study aimed to identify an accurate, reliable and easily performed standardised method for determining the correct anatomical position of the joint line intra-operatively during revision TKA. The hypothesis was that a ratio could be determined based on the distal and posterior articular distances from the epicondyles to indicate the imaginary borders of the distal femur and the level of the joint line in revision TKA, and therefore enable an accurate decision regarding the size and location of the femoral component.…”
Section: Introductionmentioning
confidence: 99%
“…Since restoration of joint line can be difficult in severe osteoarthritic knee with coronal and sagittal plane deformities, many surgeons prefer the use of a PS TKR, which is less sensitive to changes in joint line position: in fact, the level of the reconstructed joint line is one of the main factors that affects the tension of the retained PCL [21]. As reported by Emodi et al in a cadaveric study "As the joint line was elevated, PCL strain increased at all measured flexion angles above 30°…" and "…the centre of tibio-femoral contact did not change at the flexion angles of 15 and 30°…" but "…at 60, 90 and 105° the tibio-femoral contact centre moved posteriorly with each successive elevation of the joint line."…”
Section: Joint Line Positionmentioning
confidence: 99%
“…Abgesehen von der Radiendiskussion bleibt festzustellen, dass nach unserem aktuellen Verständnis der wesentliche Schlüssel zur endoprothetischen Rekonstruktion der Kniegelenkkinematik und der Stabilität in mittlerer Beugung in der möglichst anatomischen Wiederherstellung der Gelenkflächen des Femurs liegt. Es ist evident, dass eine Anhebung der Gelenklinie beispielhaft zu einer Verkürzung des Hebelarms der Kniestreckung und zu einem Anstieg des retropatellaren Drucks führt [14,15] (▶ Abb. 2).…”
Section: Introductionunclassified